PENTINGNYA SHOLAT DALAM PEMBENTUKAN WATAK SISWA DI MTs NW SENYIUR - Ayatullah Ayatullah (JIE (Journal of Islamic Education), 2018)
This study aims to: (1) find out the significance of prayer in the formation of the personality of students (2) knowing the efforts made by the teacher and parents of students in shaping their personality. This research is a qualitative research that is based on the condition of natural objects, a dynamic, the result of construction of thought, and intact which has an inseparable unity. This research was conducted at MTs. NW Senyiur. The choice of location of this study is based on the reason that this school is making improvements to prepare itself as one of the schools that excels in achievement and morals by improving the moral quality of their students, in this case by approaching spiritual values ​​such as prayer services. Prayer services in shaping the personality of students in MTs. NW Senyiur is considered very important, because with the prayer service, the teacher, parents, and students will have a very good and harmonious relationship. So that the teachers and parents of students have a sense of responsibility towards students and their children both at school and at home.